2019
DOI: 10.1002/advs.201901388
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing Hydrogels and Cryogels from Biodegradable Polyurethane Nanoparticle Crosslinked Chitosan

Abstract: Hydrogels are widely used in tissue engineering owing to their high water retention and soft characteristics. It remains a challenge to develop hydrogels with tunable degradation rates, proper environmental responsiveness, and injectability. In this study, biodegradable difunctional polyurethane (DFPU) nanoparticle dispersions are synthesized from an eco‐friendly waterborne process involving the use of glyoxal. Such DFPU is used to crosslink chitosan (CS). Schiff base linkages between DFPU and CS successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 53 publications
3
63
1
Order By: Relevance
“…DAPU was synthesized by the waterborne process through glyoxal termination of polyurethane in the final step of the polymerization, as detailed in our previous study [20]. For chemical synthesis, 10 g of PCL (soft segment) and 3 g of IPDI (hard segment) in a glass flask were reacted for 3 h with 0.05% catalyst Sn(Oct) 2 at a nitrogen atmosphere of 75 • C. Mass of 0.6699 g of DMPA (hard segment) and appropriate methyl ethyl ketone solvent were put into the flask under reflux and reacted for another hour.…”
Section: Waterborne Synthesis Of Dialdehyde Polyurethane Crosslinker (Dapu)mentioning
confidence: 99%
See 2 more Smart Citations
“…DAPU was synthesized by the waterborne process through glyoxal termination of polyurethane in the final step of the polymerization, as detailed in our previous study [20]. For chemical synthesis, 10 g of PCL (soft segment) and 3 g of IPDI (hard segment) in a glass flask were reacted for 3 h with 0.05% catalyst Sn(Oct) 2 at a nitrogen atmosphere of 75 • C. Mass of 0.6699 g of DMPA (hard segment) and appropriate methyl ethyl ketone solvent were put into the flask under reflux and reacted for another hour.…”
Section: Waterborne Synthesis Of Dialdehyde Polyurethane Crosslinker (Dapu)mentioning
confidence: 99%
“…Polyurethane films, as a kind of classic products, have a wide range of applications, including for gas barriers, flame retardants, electromagnetic interference shielding, and nerve conduits [13,14,16,17]. Additionally, polyurethanes can be modified to have different functionalities by changing the soft segments or end groups, making polyurethanes thermoresponsive, photosensitive, or crosslinkable [18][19][20]. A crosslinkable waterborne Polymers 2021, 13, 326 2 of 16 polyurethane, dialdehyde polyurethane (DAPU), has been developed recently to broaden the horizon for combining synthetic polymers with natural polymers [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticles modification with poly(1,4-butylene adipate) diol resulted in an increased susceptibility to the degradation of cryogels with 22.9% weight loss after 28 days in PBS. The obtained cryogels were pH-sensitive and could be liquefied when exposed to acetic acid (pH < 1) or in the presence of aniline with monoamine group (pH ~10) [ 171 ]. These examples show that degradation is a complex process and both environmental conditions and composition of cryogels need to be considered.…”
Section: Characterization Of the Degradation Process In Vitro And In Vivomentioning
confidence: 99%
“…Water‐based SHPs have been extensively investigated in terms of the facilitation of mechanical damage repair through hydrogen bond interaction dynamics, [ 17 , 18 , 19 , 20 , 21 , 22 ] boronic–ester bonds, [ 17 , 23 ] metal–ligand coordination, [ 24 , 25 ] and Schiff‐based imine bonds. [ 26 , 27 , 28 ] Bao's group [ 29 ] reported that when siloxane oligomers were used to construct a multiphase assembly through hydrogen bonding, the product exhibited high mechanical strength and self‐healing efficiency, but swelling remained a major concern because of the water molecules. Wang's group [ 21 ] demonstrated that a new fluorinated SHP could withstand exposure to water solutions with various pH values through the external force of dipole–dipole interaction in C—F bonds.…”
Section: Introductionmentioning
confidence: 99%